Exploration of Shopeepay Digital Wallet Usage among Accounting Education Students at Universitas Muhammadiyah Surakarta - Dewi, Intan Amelia; Jatmika, Surya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to describe the use of the ShopeePay digital wallet among students of the 2020 Accounting Education Program at the Universitas Muhammadiyah Surakarta. This study employs a qualitative approach with a case study research design. The research subjects consist of seven students from the 2020 Accounting Education Program who meet the criteria of having used the ShopeePay digital wallet application for two years and frequently using it in their daily lives. Data collection techniques include interviews, observations, and documentation. Data validity is ensured through source and technique triangulation. The data analysis technique employed is interactive data analysis, which involves data condensation, data presentation, and drawing conclusions. The research findings indicate that 1) Students tend to use ShopeePay digital wallets for purchasing credit, bills, and tickets online through the Shopee app and ordering food through ShopeeFood. 2) The reasons students use the Shopeepay digital wallet include the various conveniences it offers and the attractive promotions available when using the digital wallet.